Polish memories - Gombrowicz, Witold (Yale University Press, 2004)
Although Witold Gombrowicz's unique, idiosyncratic writings include a three-volume Diary, this voluminous document offers few facts about his early life in Poland before his books were banned there and he went into voluntary exile. Polish Memories-a series of autobiographical sketches Gombrowicz composed for Radio Free Europe during his years in Argentina in the late 1950s-fills the gap in our knowledge. Written in a straightforward way without his famous linguistic inventions, the book presents an engaging account of Gombrowicz's childhood, youth, literary beginnings, and fellow writers in interwar Poland and reveals how these experiences and individuals shaped his seemingly outlandish concepts about the self, culture, art, and society. In addition, the book helps readers understand the numerous autobiographical allusions in his fiction and brings a new level of understanding and appreciation to his life and work.